Associations of combined lifestyle index with migraine prevalence and headache frequency: a cross-sectional study from the MECH-HK study - Yunyang Deng; Harry Haoxiang Wang; Fei Wan Ngai; Dexing Zhang; Jing Qin; Xiangyan Chen; Yao Jie Xie (The Journal of Headache and Pain, 2024)
Abstract Background Prior research has shown that individual lifestyles were associated with migraine. Yet, few studies focused on combined lifestyles, particularly in Chinese populations. This cross-sectional study aimed to investigate the relationships of a combined lifestyle index with migraine in Hong Kong Chinese women. Methods Baseline data from a cohort study named Migraine Exposures and Cardiovascular Health in Hong Kong Chinese Women (MECH-HK) were used for analysis. In total 3510 women aged 55.2 ± 9.1 years were included. The combined lifestyle index comprised eight lifestyle factors: smoking, physical activity, sleep, stress, fatigue, diet, body mass index, and alcohol. Each component was attributed a point of 0 (unhealthy) or 1 (healthy). The overall index was the sum of these points, ranging from 0 (the least healthy) to 8 points (the healthiest). Migraine was diagnosed by the International Classification of Headache Disorders 3rd edition. Additionally, for women with migraine, the data on migraine attack frequency (attacks/month) was collected. Results A total of 357 women with migraine (10.2%) were identified. The prevalence of migraine for the 0–3-point, 4-point, 5-point, 6-point, and 7–8-point groups were 18.0% (162/899), 10.9% (86/788), 6.6% (51/776), 6.0% (38/636), and 4.9% (20/411), respectively. In the most-adjusted model, compared to the 0–3-point group, the odds ratios and 95% confidence intervals for the 4-point, 5-point, 6-point, and 7–8-point groups were 0.57 (0.43–0.75), 0.33 (0.24–0.46), 0.30 (0.21–0.44), and 0.25 (0.15–0.41), respectively (all p < 0.001). For each component, migraine was significantly associated with sleep, stress, fatigue, and diet; but was unrelated to smoking, physical activity, body mass index, and alcohol. Among women with migraine, per point increase in the combined lifestyle index was associated with a reduced migraine attack frequency (β = − 0.55; 95% confidence interval = − 0.82, − 0.28; p < 0.001). Conclusions A combined lifestyle index was inversely associated with migraine and migraine attack frequency in Hong Kong Chinese women. Adhering to a healthy lifestyle pattern might be beneficial to the prevention of migraine attacks. Conversely, it is also plausible that women with migraine might have a less healthy lifestyle pattern compared to those without headaches.